Employee learning in high-contact service industries. Issue 4 (31st January 2018) - Yee, Rachel W.Y.; Lee, Peter K.C.; Yeung, Andy C.L.; Cheng, T.C.E.
Abstract : Purpose: Employee learning is imperative in the dynamic service environment; yet, much is still unknown about its strategic importance. The purpose of this paper is to extend the understanding of learning by focusing on the strategic importance of learning goal orientation (LGO) in customer-contact employees in service industries characterized with high customer contact. Design/methodology/approach: This paper adopts the multi-method approach by conducting two studies in the high-contact service sector. Study 1 is a large-scale, multiple-respondent survey that investigates the associations between LGO and its antecedents and performance outcomes. To supplement study 1, study 2 embraces case studies that identify the managerial supportive practices and outcomes of customer-contact employees' learning behaviors. Findings: The results of study 1 demonstrate that employees' affective organizational commitment does not yield higher-quality services unless the service employees are learning oriented. The findings of study 1 also indicate that management commitment to service quality has positive effects on both LGO and affective organizational commitment. In study 2, the results reveal the practical methods that managers can employ to effectively promote such activities. Originality/value: This research offers novel insights into research on learning by showing the strategic importance of LGO to enhancing high-contact service firms' performance and the practical means of fostering LGO in customer-contact employees.